Completeness of Retention Data and Determinants of Attrition in Birth Cohorts of Very Preterm Infants: A Systematic Review - Teixeira, Raquel; Queiroga, Ana Catarina; Freitas, Ana Isabel; Lorthe, Elsa; Santos, Ana Cristina; Moreira, Carla; Barros, Henrique (Frontiers in Pediatrics, 2021)
Background: Birth cohorts provided essential knowledge for clinical and public health decision-making. However, little is known about retention and determinants of attrition in these specific longitudinal studies although characterizing predictors of attrition sets the path to mitigate its occurrence and to promote valid inferences. We systematically reviewed retention in follow-ups of birth cohorts of very preterm or very low birth weight infants and the determinants of attrition. PROSPERO registration number: CRD42017082672. Methods: Publications were identified through PubMed®, Scopus, Web of Science and Cochrane Library databases from inception to December 2017. Studies were included when reporting at least one of the following: retention at follow-ups, reasons for attrition, or characteristics of non-participants. Quality assessment was conducted using the completeness of the report of participation features in the articles. Non-participant’s characteristics were presented using descriptive statistics. Local polynomial regression was used to describe overall retention trends over years of follow-up. Results: We identified 57 eligible publications, reporting on 39 birth cohorts and describing 83 follow-up evaluations. The overall median retention was 87% (p25-p75:75.8- 93.6), ranging from 14.6% to 100%. Overall, retention showed a downward trend with increasing child age. Completeness of retention report was considered “enough” in only 36.8% of publications. Considering the 33 (57.9%) publications providing information on participants and non- participants, and although no formal meta-analysis was performed, it was evident that participants lost to follow up were more often male, had foreign-born, multiparous and younger mothers and a lower socioeconomic status. Conclusion: This systematic review evidenced a lack of detailed data on retention, which may threaten the potential use of evidence derived from cohort studies of very preterm infants for clinical and public health purpose. It supports the requirement for a standardized presentation of retention features responding to current guidelines.